Interpretation on withholding tax revisited: the case of the inland revenue board of Malaysia - Hazlina, Hussain (2020)
The interpretation of the withholding tax (WHT) law has been disputed since the introduction of the law as seen from the legal battle between the taxpayers and the Inland Revenue Board (IRB) and the divergent court decisions on the interpretation of the WHT law. More research on the interpretation spectrum of the WHT law introduced in 1983 as a consequence of an apex court landmark decision is warranting. The apex court decided that the management fees paid to a company resident in the United Kingdom (UK) were not subject to tax in Malaysia as it had no permanent establishment in Malaysia had caused a significant impact to the Government to collect tax from the non-resident. Hence, this study aims to investigate the interpretation of the WHT law revisited under the Income Tax Act 1967 (ITA 1967). A qualitative approach by adopting action research methodology was utilised in this research. A research action methodology by reporting six major cycles where each cycle consisted of diagnosis, planning, action-taking and evaluating was employed in this research. Data was collected from discussions with the stakeholders of the IRB, judiciary, lawyers and tax agents through focus groups and interviews were recorded, transcribed, and rigorously analysed. The results revealed that prior engagements with the stakeholders assist the Government in making a clear policy and drafting a clear WHT law. This research offers practical contribution whereby the revised WHT law has been passed by the Parliament with no appeal has been lodged to the IRB to date, inferring the improved WHT law is clearer and taxpayers seriously comply with the WHT obligations.